Hydrological modelling of flood risk and watershed response to land use change: A case study of the Anambra Watershed, Nigeria - Okpala Chukwunonso Michael (PT. Pena Produktif Kreatif, 2026)
Land use and land cover (LULC) changes significantly influence watershed hydrological processes and flood risk. This study assessed the effects of long-term LULC change on the hydrological response of the Anambra Watershed between 1995 and 2025 using Remote Sensing (RS), Geographic Information Systems (GIS), and HEC-HMS hydrological modelling. Satellite imagery was analyzed to quantify historical land cover changes, while HEC-HMS was employed to simulate rainfall–runoff responses under varying land use conditions. The results revealed a 184.2% increase in built-up areas and substantial declines in forest cover (34.1%) and wetlands (34.0%) over the study period. Hydrological simulations showed that these changes reduced infiltration by 45.4%, increased surface runoff by 36.0%, and increased peak discharge by 38.6% under a 100-year rainfall event. The time-to-peak also decreased from 14.2 to 11.8 hours, indicating a faster watershed response to storm events. Flood susceptibility mapping further revealed that approximately 73% of the watershed falls within medium to very high flood-risk categories, with the highest vulnerability concentrated in the southern floodplain regions. The findings demonstrate that long-term land use change has significantly altered the hydrological behaviour of the watershed and increased flood vulnerability. The study highlights the importance of riparian restoration, wetland conservation, and sustainable urban drainage strategies for effective flood-risk management within the watershed.